Matrix attachment region binding protein MFP1 is localized in discrete domains at the nuclear envelope. - Gindullis, F (1999)
Recently, it has been suggested that nuclear processes, such as replication, transcription, and splicing, are spatially organized and associated with a nuclear framework called the nuclear matrix, a structure of unknown molecular composition. It has been shown that chromatin is attached to the nuclear matrix via specific DNA fragments called matrix attachment regions (MARs). We have begun to dissect the plant nuclear matrix by isolating a DNA binding protein with specific affinity for MARs. Here, it is shown that MAR binding filament-like protein 1 (MFP1) is associated with specklelike structures at the nuclear periphery that are part of isolated nuclei and the nuclear matrix. A predicted N-terminal transmembrane domain is necessary for the specific targeting of MFP1 to the speckles, indicating an association with the nuclear envelope-endoplasmic reticulum continuum. In addition, it is shown that a marker protein for plant microtubule organizing centers, which has been shown to be localized on the outside of the plant nuclear envelope, is also part of the nuclear matrix. These findings indicate a close and previously undescribed connection in plants between the nuclear envelope and the internal nuclear matrix, and they suggest a function for MFP1 in attaching chromatin to specific sites at the nuclear periphery.